Use of anakinra in cryopyrin-associated periodic syndromes: case report and review of literature - Salas Sánchez, Marta; García-Martínez, Elena; Balastegui Martín, Héctor; Durán-García, María Esther; Lavilla Olleros, Cristina (Frontiers in Immunology, 2025)
Cryopyrin-associated periodic syndrome is a rare autoinflammatory syndrome caused by a dysregulation of cytokine signaling pathways, particularly of the interleukin-1β production. Symptoms typical appear early in life and include recurrent fever, arthralgia, and cutaneous rash, often accompanied by systemic manifestations and progressive end-organ damage resulting from chronic inflammation. Interleukin- targeted therapy constitutes the basis for treatment, and can lead to complete resolution of symptoms. We report a case of a 66-year-old man with cryopyrin-associated periodic syndrome related to V198M mutation, successfully treated with anakinra, an interleukin- 1 inhibitor frequently used in rheumatoid arthritis.